Indigenous Peoples' Rights in Development of the National Capital City: Between Fulfillment and Violation - Rafiqi, Ilham Dwi; Gotra, Narayana Maha; Anderson, Christine (Lex Journal: Kajian Hukum & Keadilan, 2024)
An ambitious project that aims to distribute government and economic centers more evenly in Indonesia. However, this development process faces significant challenges, one of which is related to its impact on indigenous communities inhabiting the area. This study identifies and analyzes the main problems that arise due to the development of the IKN, especially in terms of the existence and potential of indigenous peoples' rights. The research method used is normative legal research with a legislative and conceptual approach. The results of the study indicate that the rights of indigenous peoples that have been guaranteed by international and national legal instruments have been violated due to the development of the IKN. This is due to the minimal participation of Indigenous peoples in decision-making and the failure to fulfill the rights of Indigenous peoples in the IKN area, such as land rights and control of customary land, original rights, rights to develop and preserve customs, rights to recognition and protection of Indigenous peoples, and other rights. Amid the ongoing IKN development process, the government needs to take steps to restore and protect the rights of indigenous peoples. This research is expected to be part of that reference.